The Cuticular Hydrocarbons Profiles in the Colonial Recognition of the Neotropical Eusocial Wasp, Mischocyttarus cassununga (Hymenoptera: Vespidae) - Murakami, A. S. N. [UNESP]; Nunes, T. M.; Desuo, I. C. [UNESP]; Shima, S. N. [UNESP]; Mateus, S. (Univ Estadual Feira Santana, 2015)
Cuticular hydrocarbons are chemical messengers with fundamental role in information transfer on the nestmate recognition, physical or behavioral caste, age, task specialization and reproductive status among individuals of colony. In basal (primitively) eusocial wasps, the role of cuticular hydrocarbons in the colonial recognition has been extensively studied in genus Polistes (Polistinae) and Stenogastrinae. Although the genus Mischocyttarus (Polistinae) is a large group of neotropical eusocial wasps and its cuticular hydrocarbons were only investigated in a few species. This study aimed to verify whether the cuticular hydrocarbons can discriminate the intercolonial identity in Mischocyttarus cassununga. Our results showed that the cuticular hydrocarbons potentially can play a role in intercolony recognition.
Keywords: Recognition nestmate; Chemical signal; Colony; Mischocyttarini